CARDIAC ARRHYTHMIAS AND LEFT VENTRICULAR HYPERTROPHY IN SYSTEMIC HYPERTENSION - Sultana, Riffat; Sultana, Nuzhat; Rashid, Abdul; Rasheed, Syed Zahid; Ahmed, Mansoor; Ishaq, Muhammad; Samad, Abdus (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hypertensive left ventricular hypertrophy (LVH) is associated with increased risk of arrhythmias and mortality. Objective was to investigate the prevalence of cardiac arrhythmias and LVH in systemic hypertension. Methods: In all subjects blood pressure was measured, electrocardiography and echocardiography was done. Holter monitoring and exercise test perform in certain cases. There were 500 hypertensive patients, 156 (31.2%) men and 344 (69%) women >30 years of age in the study. Among them 177 (35.4%) were diabetic, 224 (45%) were dyslipidemia, 188 (37.6%) were smokers, and 14 (3%) had homocysteinemia. Duration of hypertension (HTN) was ‰¥2 years). Mean systolic BP (SBP) was 180±20 mm Hg and diastolic BP (DBP) was 95±12 in male and female patients. Left ventricular mass index (LVMI) was 119.2±30 gm/m2 in male while 103±22 gm/m2 in female patients. Palpitation was seen in 126 (25%) male and 299 (59.8%) female patients. Atrial fibrillation was noted in 108 (21.6%) male and 125 (25%) female patients, 30 (6%) male and 82 (16.4%) female patients had atrial flutter. Ventricular tachycardia was noted in 37 (7.4%) male and 59 (11.8%) female patients. Holter monitoring showed significant premature ventricular contractions (PVC'S) in 109 (21.8%) male and 128 (25.69%) female patients while Holter showed atrial arrhythmias (APC'S) in 89 (17.8%) males and 119 (23.8%) females. Angiography findings diagnosed coronary artery disease in 119 (23.8%) with CAD male and 225 (45%) without CAD while 47 (9.4%) females presented with CAD and 109 (21.8%) without CAD. Conclusion: A significant association has been demonstrated between hypertension and arrhythmias. Diastolic dysfunction of the left ventricle, left atrial size and function, as well as LVH have been suggested as the underlying risk factors for supraventricular, ventricular arrhythmias and sudden death in hypertensives with LVH. Keywords: Hypertension, arrhythmias, left ventricular hypertrophy, coronary artery disease